Urogenital schistosomiasis among pre-school and school aged children in four districts of north western Tanzania after 15 years of mass drug administration: Geographical prevalence, risk factors and performance of haematuria reagent strips. - Humphrey D Mazigo; Upendo J Mwingira; Maria M Zinga; Cecilia Uisso; Paul E Kazyoba; Safari M Kinung'hi; Francesca Mutapi (Public Library of Science (PLoS), 2022)
Background Urogenital schistosomiasis remains as a public health problem in Tanzania and for the past 15 years, mass drug administration (MDA) targeting primary school children has remained as the mainstay for its control. However, after multiple rounds of MDA in highly risk groups, there are no data on the current status of Schistosoma haematobium in known endemic areas. Furthermore, the performance of commonly used diagnostic test, the urine reagent strips is not known after the decline in prevalence and intensities of infection following repeated rounds of treatment. Thus, after 15 of national MDA, there is a need to review the strategy and infection diagnostic tools available to inform the next stage of schistosomiasis control in the country. Methods/findings A analytical cross-sectional study was conducted between October and November, 2019 among pre-school (3-5years old) and school aged children (6-17 years old) living in four (4) districts with low (<10%) and moderate (10%-<50%) endemicity for schistosomiasis as per WHO classification at the start of the national control programme in 2005/06, with mean prevalence of 20.7%. A total of 20,389 children from 88 randomly selected primary schools participated in the study. A questionnaire was used to record demographic information. A single urine sample was obtained from each participant and visually examined for macrohaematuria, tested with a dipstick for micro-haematuria, to determine blood in urine; a marker of schistosome related morbidity and a proxy of infection. Infection intensity was determined by parasitological examination of the urine sample for S. haematobium eggs. Overall, mean infection prevalence was 7.4% (95%CI: 7.0-7.7, 1514/20,389) and geometric mean infection intensity was 15.8eggs/10mls. Both infection prevalence (5.9% versus 9%, P<0.001) and intensity (t = -6.9256, P<0.001) were significantly higher in males compared to females respectively. Light and heavy infections were detected in 82.3% and 17.7% of the positive children respectively. The prevalence of macrohaematuria was 0.3% and that of microhaematuria was 9.3% (95%CI:8.9-9.7). The sensitivity and specificity of the urine reagent strip were 78% (95%CI: 76.1-79.9) and 99.8% (95%CI: 99.7-99.9). Having light (P<0.001) and heavy infection intensities (P<0.001) and living in the study districts increased the odd of having microhaematuria. Predictors of S. haematobium infection were being male (P<0.003), microhaematuria (P<0.001), and living in the three study districts (P<0.001) compared to living at Nzega district. Conclusion The findings provide an updated geographical prevalence which gives an insight on the planning and implementation of MDA. Comparing with the earlier mapping survey at the start of the national wide mass drug administration, the prevalence of S. haematobium infection have significantly declined. This partly could be attributed to repeated rounds of mass drug administration. The urine reagent strips remain as a useful adjunct diagnostic test for rapid monitoring of urogenital schistosomiasis in areas with low and high prevalence. Based on prevalence levels and with some schools having no detectable infections, review of the current blanket mass drug administration is recommended.